INFORMAÇÃO GOVERNAMENTAL:PROPOSTA DE CLASSIFICAÇÃO - Bellas, Claudia Moreno (2004)
This work searches circumstances that signal the involvement of observation, registration, maintenance and capture of data and formation of groups of data, that, associated, are parts for the composition of information that, through systems, collaborate to sustain actions of the Public Administration. It has as main objective the understanding as where, in the process of composition of the information at the base and tips of the organization, are located fragilities that affect the final result of the information that support government decisions.